Technology status to treat PFAS-contaminated water and limiting factors for their effective full-scale application - C. S. Tshangana; S. T. Nhlengethwa; S. Glass; S. Denison; A. T. Kuvarega; T. T. I. Nkambule; B. B. Mamba; Pedro J. J. Alvarez; A. A. Muleja (npj Clean Water)
Abstract Per- and polyfluoroalkyl substances (PFAS) are a class of synthetic chemicals that are highly resistant to degradation because of the strong C-F bond and their unique physico-chemical properties. Several techniques, both destructive and non-destructive, have been explored for removing PFAS from contaminated water. However, the most desirable techniques, ideally capable of effective separation and complete PFAS destruction and mineralization, have not progressed beyond bench-scale testing. This paper provides an overview of the existing treatment techniques demonstrated at laboratory, pilot, and industrial scales, and their associated treatment mechanisms. Insufficient data on pilot-scale and full-scale applications for PFAS remediation has limited the optimization and advancement of these systems at a large scale. Most research related to PFAS-remediation is based on laboratory-scale studies under ideal conditions that do not represent the complexity of PFAS-contaminated media. Factors such as inhibition by competing background compounds and secondary water or air pollution limit the application of some PFAS removal techniques at full-scale. Additionally, high energy intensity, cost, and inappropriate reactor design restrict the scalability of some proposed innovations. Here, we propose integrated systems and treatment trains as potential approaches to effectively remove and destroy PFAS from contaminated waters. This review also offers and contextualizes implementation barriers and scalable approaches for PFAS treatment.